Factors influence student’s online purchase intention through travel agency sites / Muhammad Farid Sabri - Sabri, Muhammad Farid (Faculty of Business and Management, 2018)
The issue of this research is for student’s online purchase intention through travel agency sites. There are increasing number that students that buying products and services from travel agency sites being cheated. This is because there are many reasons why customers always being cheated by travel agency sites such as offering lower price packages. The results of this research are based on these two objectives. General objective is to identify factors influence students online purchase intention through agency sites. Second is to identify the significant relationship between personal security, uncertainty, customer loyalty, and customer satisfaction with student’s online purchase intention through travel agency sites. Lastly is to identify the most important factor that influence students online purchase intention through travel agency sites. The methodology for this research are first is multiple regression was used for analyze the first objective. Next is coefficient correlation analysis was used to achieves the second objective. Data was gathered by distribute questionnaire to students at UiTM Kampus Bandaraya Melaka. Then, the data are analyzed using SPSS (Statistical Package for the Social Science) version 22.0. The findings of this research are first, customer loyalty is not having relationship with online purchase intention. Last finding is customer satisfaction are the most important factor that influence online purchase intention.